A youth curfew: A retrospective view of the rise, fall and legacy of the Northbridge Policy: A - Cooper, Trudi (2017)
This article presents policy, practice and theory implications of a case study of a youth curfew. The original case study of the Northbridge Policy Project set out to document the purposes of the Northbridge Policy, how policy was implemented, and to evaluate the effectiveness of this approach as a generalised response to child welfare and youth crime. The study synthesised data from multiple sources. The original study concluded that although the project was well resourced, well managed and had improved greatly inter-agency collaboration for child protection, these benefits could have been achieved without the curfew, which undermined some preventative aspects of the project. The evaluation also concluded that previously documented successes of the curfew for crime protection and child protection had been achieved through displacement of young people to other locations that neither reduced crime nor increase safety. After the project was suddenly curtailed, analysis used moral panic theory to examine the legacy of the Northbridge curfew in terms of discourse about young people and legitimation of subsequent practices in youth policing. The analysis found that the legacy had been unhelpful because it reinforced the erroneous beliefs that the curfew had been an effective and necessary component of strategy